Chronic Pain after Laparoscopic Inguinal Hernia Repair Depends on Mesh Implant Features: A Clinical Randomised Trial - Mike Ralf Langenbach; Alexandre Berengolts (Open Journal of Pain Medicine - Peertechz Publications, 2017)
Chronic pain is a severe complication of mesh-based inguinal hernia repair. In this prospective,clinical, randomized, double-blind study we investigated the biocompatibility of three different meshes and their infl uence on chronic pain. One hundred eighty male patients with primary inguinal hernia undergoing laparoscopic transabdominal polypropylene plastic (TAPP) were randomized for using a heavyweight (108 g/m2), double-fi lament polypropylene mesh (Prolene, 10X15 cm, group A, n = 60), a multifi lament, heavyweight variant (116 g/m2) of polypropylene mesh (Serapren, 10X15 cm, group B, n = 60), or a composite mesh (polyglactin / polypropylene) (Vypro II, 10X15 cm, group C, n = 60). Groups were  compared in terms of complications, pain development and life quality (SF-36 Health Survey).  Convalescence in group A lasted more time than in groups B and C: mean-term values of the visual scales for pain development were signifi cantly higher (p<0.05), incapacity for work was 8.2 days longer, and urological adverse effects were stronger. The mean-term development of life quality was signifi cantly lower in group A up to the 12th week. There were no signifi cant differences between groups B and C. Beyond the 12th postinterventional week the differences were not statistically signifi cant. Independent of the mesh implanted there was still 5% of patients suffer chronic pain 60 months later.